Chamuangone-rich rice bran oil ameliorates neurodegeneration in AlCl3/D-galactose model via modulation of behavioral, biochemical, and neurochemical parameters - Alotaibi, Badriyah S.; Saleem, Uzma; Farrukh, Maryam; Waseem, Sadaf; Chauhdary, Zunera; Alsharif, Ifat; Alqahtani, Wedad Saeed; Alanzi, Abdullah R.; BinMowyna, Mona N.; Ajmal Shah, Muhammad; Anam, Khairul; Alanazi, Yasmene F.; et al. (Italian Journal of Food Science, 2024)
Chamuangone is an exotic medicinal compound isolated from Garcinia cowa leaves. It shows great potential against inflammation, neurodegeneration, and oxidation. Through green extraction method, chamuangone-rich rice bran oil (CRBO) containing 1.97 mg/mL of chamuangone was obtained. This research study investigates the therapeutic effects of CRBO on D-galactose- and aluminum chloride (AlCl3)-induced Alzheimer’s disease in rat model. In all, 30 rats were divided into six groups and treated for 42 days as follows: control group (vehicle), disease control group (AlCl3 150 mg/kg + D-galactose 150 mg/kg p.o.), standard group (rivastigmine 3 mg/kg p.o.), and CRBO treatment groups with doses of 2.5, 5.0, and 7.5 mg/kg p.o. Neurobehavioral studies were performed on completion of 42 days. Furthermore, biochemical, neurochemical, and histopathological analyses were performed. CRBO treatment mitigated impairment in neuromuscular coordination, mentation and cognition in behavioral tasks. It potentially recovered (p < 0.001) the declined level of catalase, superoxide dismutase, reduced glutathione and lipid peroxidation. Neurochemical analysis revealed the restoration of serotonin, noradrenaline, and dopamine concentration in the brain after CRBO treatment. Histopathological examination of vital organs revealed recovery in CRBO-treated rats in a dose-dependent manner. Owing to neurotoxic effects of inducing agents, the level of acetylcholinesterase decreased in disease control group; however, CRBO treatment recovered the declined activity of this enzyme. Therefore, it is concluded that CRBO significantly recovered the neurodegenerative effects through multiple pathways, such as amelioration of oxidative stress and neuronal plasticity. Therefore, this innovative green remedy can be considered as a natural alternative for treating neurodegenerative disorders.